Beliefs about memory decline in aging do not impact judgments of learning (JOLs): A challenge for belief-based explanations of JOLs. - Tauber, Sarah K.; Witherby, Amber E.; Dunlosky, John (Memory & Cognition, 2019)
The cue-utilization framework (Koriat, 1997) and the analytic processing theory (Dunlosky, Mueller, & Tauber, 2015) identify people's beliefs about their memory as central to how judgments of learning (JOLs) are made. This assumption is supported by ample evidence. However, researchers have almost exclusively explored the impact of participants' beliefs about the materials or the learning task, and none have evaluated the impact of beliefs about a person on JOLs. Thus, to inform JOL theory, we evaluated the degree to which JOLs are related to the belief that "memory declines with aging in adulthood." In seven experiments, college-aged participants studied words, made JOLs, and took a memory test. Participants made JOLs predicting memory performance for an average younger adult (i.e., 18–21 years old) or for an average older adult (i.e., 65+ years old). Most important, beliefs about aging in adulthood were not always sufficient to produce cue effects on JOLs, which contrasts with expectations from the aforementioned theories. An important challenge for future research will be to discover factors that moderate belief effects. To guide such explorations, we discuss possible explanations for why beliefs about aging would have demonstrated little to no relationship with people's JOLs.